Smoke Gets in Your Eyes: Student environmentalism in the Palembang haze in Indonesia. Issue 136 (2nd September 2018) - Nilan, Pamela
ABSTRACT: This article looks at the environmental discourses articulated by university students attending Universitas Sriwijaya (UNSRI) in Palembang, South Sumatra, during the 2014 annual burning season when land is illegally cleared to extend palm oil plantations. The smoke was so thick it was hard to breathe. Yet the young activists often made no initial reference to the smoke. When asked directly, they used normalising discourses to talk about the smoke. Below, the three main discourses about smoke that emerged from the interviews are discussed in detail. It is argued that these three identified discourses point to a specific regime of truth (Foucault) about the annual smoke that may point to local thinking about this important environmental problem.